Penggunaan Transcranial Magnetic Stimulation pada Fungsi Motorik Pascastroke - Christopher Lampah; Devan Perwira; Lidwina Sengkey (UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACT: Stroke is an acute neurovascular disorder that causes long-term limitations to activities of daily living and death worldwide, affecting nearly 800,000 people each year in the US, leaving sufferers with motor and cognitive impairment. Until now, scientists have only been able to understand which areas of the brain play specific roles by studying patients suffering from brain injuries. Repetitive Transcranial Magnetic Stimulation (rTMS) is a non-invasive, painless method for modulating cortical excitability. rTMS and exercise can be used to alter brain tissue and reorganize functional connections between brain regions, further promoting the recovery of motor function in stroke patients. The combination of these two therapies shows benefits in regulating cortical excitability and improving motor performance in stroke patients. Keywords: stroke; rTMS; neuroplasticity; activity daily living ABSTRAK: Stroke adalah gangguan neurovaskular akut yang menyebabkan keterbatasan jangka panjang terhadap aktivitas hidup sehari-hari dan kematian di seluruh dunia, mengenai hampir 800.000 orang setiap tahun di AS, menyebabkan penderita mengalami gangguan motorik dan kognitif. Hingga saat ini, para ilmuwan hanya dapat memahami area otak mana yang memainkan peran spesifik dengan mempelajari pasien yang menderita cedera otak. Repetitive Transcranial Magnetic Stimulation (rTMS) adalah metode non-invasif, tanpa rasa sakit untuk memodulasi rangsangan kortikal. rTMS dan latihan fisik dapat digunakan untuk mengubah jaringan otak dan mengatur kembali koneksi fungsional antara daerah otak, selanjutnya mempromosikan pemulihan fungsi motorik pada pasien stroke. Kombinasi dari kedua terapi ini menunjukkan keuntungan dalam mengatur rangsangan kortikal dan meningkatkan kinerja motorik pasien stroke. Kata Kunci: stroke; rTMS; neuroplastisitas; aktivitas kehidupan sehari-hari